Effective gas permeability of Tight Gas Sandstones as a function of capillary pressure – a non‐steady‐state approach. Issue 3 (16th October 2015) - Amann‐Hildenbrand, A.; Dietrichs, J. P.; Krooss, B. M.
Abstract: Single‐ and two‐phase (gas/water) fluid transport in tight sandstones has been studied in a series of permeability tests on core plugs of nine tight sandstones of the southern North Sea. Absolute (Klinkenberg‐corrected) gas permeability coefficients ( k gas _inf ) ranged between 3.8 × 10 −16 and 6.2 × 10 −19 m 2 and decreased with increasing confining pressure (10–30 MPa) by a factor 3–5. Klinkenberg‐corrected (intrinsic) gas permeability coefficients were consistently higher by factors from 1.4 to 10 than permeability coefficients determined with water. Non‐steady‐state two‐phase (He/water) flow experiments conducted up to differential pressures of 10 MPa document the dynamically changing conductivity for the gas phase, which is primarily capillary‐controlled (drainage and imbibition). Effective gas permeability coefficients in the two‐phase flow tests ranged between 1.1 × 10 −17 and 2.5 × 10 −22 m², corresponding to relative gas permeabilities of 0.03% and 10%. In the early phase of the nonstationary flow regime (before establishment of steady‐state conditions), they may be substantially (>50%) lower. Effective gas permeability measurements are affected by the following factors: (i) Capillary‐controlled drainage/imbibition, (ii) viscous–dynamic effects (iii) and slip flow. Abstract : Single‐ and two‐phase (gas/water) permeability experiments were carried out on nine tight sandstones from the Southern North Sea. Intrinsic (water) permeability coefficients ranged from 10 −16 to 10 −19 m 2 . Relative gas permeability coefficients established during successive drainage ranged between 0.03% and 10% of the steady state Klinkenberg‐corrected gas permeability coefficients. Gas permeability coefficients after capillary breakthrough clearly increase with increasing pressure difference, confirming capillary pressure‐controlled change in gas saturation.